2013
DOI: 10.5539/ijc.v5n1p39
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Silsesquioxane Organically Modified with 4-amino-5-(4-pyridyl)-4H-1,2,4-triazole-3-thiol (APTT) for Adsorption of Metal Ions

Abstract: This paper describes the preparation of a nanostructured silsesquioxane, the cloropropilsilsesquioxano (S) that was organofunctionalised with the 4-amino-5-4(pyridyl)-4H-1,2,4-triazole-3-thiol (APTT), the material obtained of the functionalization was described as SA. The material SA was characterized by spectroscopy in the region of infrared (FTIR). After proper characterization, were carried studies on adsorption of metallic ions such as Cu 2+ , Ni 2+ and Cd 2+ in the active sites of SA. Different methods we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The FTIR spectrum of the APTT, SS, and one formed by reaction of SS with APTT (SA) and CuHSA was detailed in recent reports [27,41]. In these studies, an absence of the band at 590 cm −1 related to the C-Cl vibrations was observed as main spectral characteristic, therefore confirming the organofunctionalization of SA.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 74%
“…The FTIR spectrum of the APTT, SS, and one formed by reaction of SS with APTT (SA) and CuHSA was detailed in recent reports [27,41]. In these studies, an absence of the band at 590 cm −1 related to the C-Cl vibrations was observed as main spectral characteristic, therefore confirming the organofunctionalization of SA.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 74%
“…A copper wire was inserted through the opposite end of the glass tube to establish electrical contact. The modified paste, after homogenization, was positioned on the tube tip to avoid possible air gaps, which often enhance electrode resistance [22].…”
Section: Preparation Of the Graphite Paste Electrode Modified With CDmentioning
confidence: 99%
“…The prepared material was oven vacuum dried at 100 °C for 4 hours. Figure 1 illustrates (Soares, Silveira, Silvestrini, Bicalho, & Do Carmo, 2013) a scheme of this syntheses:…”
Section: Preparation Of Octa-(3-chloropropyl)octasilsesquioxane With mentioning
confidence: 99%
“…The functionalization of octa-(3-chloropropyl)octasilsesquioxane (S) (Figure 1) was performed, as describe in the literature (Soares, Silveira, Silvestrini, Bicalho, & Do Carmo, 2013): reacting 9.70×10 -3 mol of S, with 8.70×10…”
Section: Preparation Of Octa-(3-chloropropyl)octasilsesquioxane With mentioning
confidence: 99%